Demographic and socio-economic morphology of Chinese communities in Iloilo City before the war a microhistory in urban space - Madrid, Randy M. (Danyag :the UPV journal of humanities and social sciences, 2009)
"This paper tackles the demographic and socio-economic morphology of Chinese communities in pre-war Iloilo City. It focuses on the development of socio-economic structures like the emergence of a Chinatown, the formation of Chinese schools, and the Chinese monopoly in the retail trade, that greatly influenced the Chinese demographic make-up in Iloilo City. Demographic issues like ethnicity and hybridity are discussed in relation to the Chinese presence in the city, which is a concrete representation of a microhistoric space. The data presentation and analysis are heavily reliant on fiscal indices and archival materials like old Chinese records (i.e. Chinos Provincianos), old files on Iloilo City economy (i.e. Fincas Urbanas), pre-war newspapers and periodicals (i.e. Ang Makinaugalingon), and pre-war demographic profiles (i.e. Census in the Philippine Islands, 1939). Source materials on Chinatowns in the Philippines and in other parts of the globe, the socio-economic situation of the Chinese communities in the Philippines before the war, the Chinese Exclusion Act of 1902, and the Filipino-Chinese relations, are also included in the study."